DEVELOPING QUARTET CARDS AS AN INFORMATIONAL TOOL PREVENTING BULLYING AMONG STUDENTS AT SDN 246/IX, PEMATANG GAJAH VILLAGE - Anggraini, Dinda; Rahman, K A; Zulfikar, Muhammad (Jurnal Kopendik, 2025)
Bullying in schools negatively affects students’ emotional, social, and academic development. This study aims to develop a quartet card learning medium as an informational tool for bullying prevention among elementary school students. The research employed a Research and Development (R&D) approach using the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The product was validated by material experts, media experts, and teachers, and tested on fourth-grade students in small and large groups. Results indicated high feasibility, with scores of 93% from material experts, 88.75% from media experts, and 89% from teachers, as well as positive student responses of 94% and 97%. The medium effectively enhanced students’ understanding and awareness of bullying forms, impacts, and prevention. The study implies that quartet cards can serve as an alternative educational tool in guidance and counseling services and offers originality through a 3D-illustrated design aligned with students’ cognitive development stages.